Letter to Jane Tolmach from Thomas N. Saunders - Thomas N. Saunders:::::: (1968)
This February 9, 1968 correspondence from the California Democratic Presidential Delegation Committee provides Jane Tolmach with logistical and procedural information regarding her participation on the Delegation Selection Committee. The committee was scheduled to meet February 17–18, and members were asked to confirm attendance and arrange accommodations. Enclosed materials included forms to recommend potential delegates and affidavits required for delegate candidates. A memorandum from Charles Warren explains that all 174 delegate affidavits must be filed with the Secretary of State before petitions can circulate, with a goal of filing by March 4 to allow time to gather 14,000 signatures. Tolmach is asked to complete and return two signed copies of her affidavit promptly to facilitate the process.